(3OjhGf YKeGf GdHUQjs - (3YKeGf Hf SfO GdfLOj GdHUQj, HOQ GdOjf, GHf SfO , J (B1242 (3g` s
(3ChdgG (B:s
(3hdO SfI (B1237 (3EQJLGdkG, hbO CQSd dg HYV GdHZOGOjjf jWdH UfOhbkG(B: (3Ef QeJ UfOhb SmQ aj efGRdfG aeG hLOfG HgG ddSQ UfOhbkG s
(3BNQgG (B:s
(3ajG hGdO GdfLd gfFJg ceG gfFrJ HGHf bjS Jeje aEf QeJ JGQjNg SjOj abrhdj Ydi fHjd YXje s
(3HYV ef GdOjhGf efShN HNW GdTGYQ GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B367s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B155 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdCOHs